The structure and electronic properties of the MoSe2/PtS2 van der Waals heterostructure. Issue 33 (12th August 2022) - Zhang, Hui; Pei, Meng; Liu, Boyang; Wang, Zongli; Zhao, Xu
Abstract : The tunable band alignment of the MoSe2 /PtS2 heterostructure from the type-I band alignment to the type-II one can be realized. Abstract : The structure and electronic properties of the MoSe2 /PtS2 van der Waals heterostructure and their dependence on the interlayer coupling, biaxial strain and external electric field are systematically investigated by using first-principles calculations. Herein, six stacking patterns are taken into consideration. The most energy favorable one is the AC stacking pattern, which is an indirect band gap semiconductor with type-I band alignment. The interlayer coupling, biaxial strain and external electric field can not only tune the band alignment of the MoSe2 /PtS2 heterostructure from type-I band alignment to the type-II one, but also effectively modulate the band gap, ranging from 0 eV to 0.805 eV. These interesting properties induced by interlayer charge transfer, such as tunable band gaps and the characteristic of type-II band alignment, are beneficial for the application of the 2D MoSe2 /PtS2 van der Waals heterostructure in future electronic and optoelectronic devices.